2019
DOI: 10.1111/ncmr.12157
|View full text |Cite
|
Sign up to set email alerts
|

Big Questions for Negotiation and Culture Research

Abstract: On April 12, 2018, at the Kellogg School of Management at Northwestern University, we hosted a conference on the frontiers of culture and negotiation research. The conference brought together scholars from two vibrant areas of research-cultural psychology and negotiation-in order to stimulate future research at the intersection of culture and negotiation.For years, these two areas remained isolated from each other: Negotiation research, which developed in the West, tended to ignore culture. Culture research, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…This term is used interchangeably with characteristic or feature . The characteristics most often studied in negotiation have been sex (Kennedy & Kray, 2015; Mazei et al, 2015), culture (Gelfand & Brett, 2004), and personality traits (Barry & Friedman, 1998).…”
Section: Individual Differences In Negotiationmentioning
confidence: 99%
See 1 more Smart Citation
“…This term is used interchangeably with characteristic or feature . The characteristics most often studied in negotiation have been sex (Kennedy & Kray, 2015; Mazei et al, 2015), culture (Gelfand & Brett, 2004), and personality traits (Barry & Friedman, 1998).…”
Section: Individual Differences In Negotiationmentioning
confidence: 99%
“…That is, the study of person-level effects cannot lose sight of the fact that negotiation is inherently relational. Along these lines, research has examined the interaction effect of same versus other sex dyads (Kray & Thompson, 2005) and same versus other culture dyads (Gelfand & Brett, 2004). Recent work has started to look at the interaction effect of personality traits.…”
Section: Empirically Testing the Modelmentioning
confidence: 99%
“…The view of negotiation as a process is based on the idea that negotiations are acts of communication between different parties that have different preferences, but are trying to find ways to collaborate and to reach an agreement (Lempereur and Pekar, 2017; Jochemczyk and Nowak, 2010; Butt et al , 2005; Murnighan et al , 1999; Putnam and Roloff, 1992). One way of describing negotiation communication processes in the extant literature is in terms of integrative and distributive processes (Gelfand and Brett, 2004). The idea of integrative and distributive processes is prominent within the field of business negotiation research and is based on a study by Walton and McKersie (1965), who suggested that a negotiation process consists of four sub-processes: distributive bargaining, integrative bargaining, attitudinal bargaining and intra-organizational bargaining.…”
Section: Conceptual Aspects Of Business Negotiationmentioning
confidence: 99%
“…Cultural transition could be a self-motivated and active construction performed by individuals, and negotiation as an ongoing process (Gelfand & Brett, 2004). Understanding cultural transition is a central requirement in understanding negotiation, as it may indicate a negotiator's tendency to think that negotiation is primarily a process of building, reconstructing and maintaining relationships, or a process of distributing resources.…”
Section: Culture and Culture As Transitionmentioning
confidence: 99%